THE ROUTLEDGE INTERNATIONAL HANDBOOK OF CHILD AND ADOLESCENT GRIEF IN CONTEMPORARY CONTEXTS - Breen, Lauren J.; Breen, Lauren J.; Traher, Carrie (Taylor & Francis Routledge [Imprint], 2023)
death, grief, bereavement, youth, childhood, child, adolescence, non-death losses, illness, disability, pandemic, COVID-19, Black Lives Matter, BLM, parents, siblings, climate change, environmental grief, immigration, relocation, sexual exploitation, social media, war, oppression
eng
Keywords: Grief in adolescence; Grief in children; Loss (Psychology) in adolescence; Loss (Psychology) in children; Chagrin chez l'adolescent.; Chagrin chez l'enfant.; Perte chez l'adolescent.; Perte chez l'enfant.; FAMILY & RELATIONSHIPS / Death, Grief, Bereavement; Grief in adolescence; Grief in children; Loss (Psychology) in adolescence; Loss (Psychology) in children; PSYCHOLOGY / Psychotherapy / Child & Adolescent; adolescence; bereavement; Black Lives Matter; BLM; child; childhood; climate change; COVID-19; death; disability; environmental grief; grief; illness; immigration; non-death losses; oppression; pandemic; parents; relocation; sexual exploitation; siblings; social media; war; youth